Development of a Web Based Badminton Court Rental Information System with the Laravel Framework - Muhammad Rizal Adinoval; Rizkysari Mei Maharani; Ahmad Jazuli (International Journal of Science and Environment (IJSE), 2026)
The rental process of badminton courts in Sengonbugel, Mayong, Jepara is still predominantly conducted manually, such as by visiting the location directly or through communication media like telephone and WhatsApp. This manual process often leads to various problems, including limited access to court schedule information, the risk of double booking due to the absence of an integrated recording system, and inefficiencies in administrative procedures for both users and court managers. This study aims to design and develop a web-based badminton court rental information system that facilitates online reservation, provides real-time court availability information, and assists managers in managing rental data, schedules, and transactions in a more structured manner. The research method consists of system requirements analysis, system design, and system implementation. The system is developed using the Laravel framework with MySQL as the database management system. The features provided include court booking, schedule and rental duration selection, payment proof upload, and an admin dashboard for managing courts, bookings, and schedules. The results show that the web-based badminton court rental information system is able to improve the efficiency of the rental process, reduce recording errors and the occurrence of double booking, and enhance the quality of services for both users and court managers.